2014
DOI: 10.1186/2193-1801-3-193
|View full text |Cite
|
Sign up to set email alerts
|

A synergetic combination of small and large neighborhood schemes in developing an effective procedure for solving the job shop scheduling problem

Abstract: This paper presents an effective procedure for solving the job shop problem. Synergistically combining small and large neighborhood schemes, the procedure consists of four components, namely (i) a construction method for generating semi-active schedules by a forward-backward mechanism, (ii) a local search for manipulating a small neighborhood structure guided by a tabu list, (iii) a feedback-based mechanism for perturbing the solutions generated, and (iv) a very large-neighborhood local search guided by a forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In the data energetic world, collection and generation of data are important, data can be extracted from the machine sensors in form of quality data, product data infrastructure data, process data, plant data, logistics data,and data from partners [11]. New methods for processing, management, and storing of such data are required also to use and gain the actual benefits from the data, new visualization techniques, algorithms, products, and models are required [12]. Companies are facing a shortage of skilled staff due to various factors.…”
Section: Production Flow Conceptmentioning
confidence: 99%
“…In the data energetic world, collection and generation of data are important, data can be extracted from the machine sensors in form of quality data, product data infrastructure data, process data, plant data, logistics data,and data from partners [11]. New methods for processing, management, and storing of such data are required also to use and gain the actual benefits from the data, new visualization techniques, algorithms, products, and models are required [12]. Companies are facing a shortage of skilled staff due to various factors.…”
Section: Production Flow Conceptmentioning
confidence: 99%
“…However, the different scheduling rules produce different performances or complexity of a system (Chuen and Robert 1993 ; Grabot and Geneste 1994 ; Holthaus and Rajendran 1997 ; Amirghasemi and Zamani 2014 ; Nurre and Sharkey 2014 ; Xu et al 2015 ; Zeng et al 2015 ). The comparative analysis of scheduling rules in some specific industrial environments can be found in Rajendran and Holthaus ( 1999 ), Kizil et al ( 2006 ), Chiang and Fu ( 2007 ), Akturk ( 2011 ), and Li et al ( 2015 ).…”
Section: Influence Of the Scheduling Rules On Line- Seru mentioning
confidence: 99%
“…ORB problem contains ten 10 × 10 instances. To illustrate the effectiveness, the proposed multiparent crossover is compared with the other algorithms such as synergistically combining small and large neighborhood schemes (SLENP) [31], parallel genetic algorithms (PGA) [13] with two-parent crossover, and greedy randomized adaptive search procedure (GRASP) [32]. The relative errors (REs) are calculated based on deviation between BKS and the best solution found (Best).…”
Section: Comparison With Differentmentioning
confidence: 99%